(untitled) (Annals of Medical Research, 2021)
Aim: MBL E test for MBL screening in carbapenem resistant Pseudomonas aeruginosa isolates is recommended as a fast and reliable phenotypic screening test. However, as it has been put forward by some reserachers, because of variations in antibiotic susceptibility tests or MBL E test with different brands of Müeller- Hinton Agar (MHA) media, the possibility that carbapenem MIK values and MBL E test results can, therefore, be influenced by these media. To this end, we aim to determine the most suitable MHA media to be used in search for MBL E test in routine microbiology laboratories by employing five different brands of MHA media.